Etika Distribusi Dalam Ekonomi Islam - Atok Syihabuddin (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Humans interact with other humans to exchange potentials, whose goal is to create more diverse interactions. In this interaction sometimes humans become predators for other humans. Under these conditions, Islam is present to impose its limitations, in the form of news, orders, and prohibitions. One of the prohibitions in the Qur'an is the spin and the circulation of wealth only on the wealthy people, so it needs to be a fair distribution of wealth. The discussion in this paper begins with a discussion of the distribution and ethics, so that raises the various concepts of ethical axioms of some of the opinions of Muslim Economists. The Islamic economic system departs from an awareness of ethics, in contrast to other economic systems. Furthermore, will be described Islamic philanthropy as a manifestation of the axiom of distribution ethics, both obligatory and sunnah philanthropic. Through these philanthropic teachings, Islam wants to reduce the negative nature of human beings, even make it as a buffer of Islam (Rukun Islam). That is, without implementing it means someone's Islam will collapse. This is a realistic account of the ethical distribution initiated by Islam. Implementation of Islamic philanthropy and accompanied by knowledge of sharia is the first step in the form of community welfare.